2017
DOI: 10.1016/j.pt.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Immune Responses, Microbiota, and Pathogenesis in Giardiasis

Abstract: Giardia lamblia is one of the most common infectious protozoans in the world. Giardia rarely causes severe life-threatening diarrhea, and may even have a slight protective effect in this regard, but it is a major contributor to malnutrition and growth faltering in children in the developing world. Giardia infection also appears to be a significant risk factor for post-infectious irritable bowel and chronic fatigue syndromes. In this review we highlight recent work focused on the impact of giardiasis and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 120 publications
(149 reference statements)
2
76
0
7
Order By: Relevance
“…A role for mast cells in controlling the G. intestinalis infection has been demonstrated in vivo in several different animal models [19,20]. Earlier studies in mice used animals less than 10 weeks of age that were treated with antibiotics before the challenge infection [7,8,22,35,61,62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A role for mast cells in controlling the G. intestinalis infection has been demonstrated in vivo in several different animal models [19,20]. Earlier studies in mice used animals less than 10 weeks of age that were treated with antibiotics before the challenge infection [7,8,22,35,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that G. intestinalis can secrete a large number of immunomodulatory proteins, possibly regulating host immune responses [13][14][15][16]. However, the mechanisms on how interactions between the host and Giardia either lead to parasite clearance or to disease remain to be understood.Recent studies have shown the importance of different immune cells in giardiasis, where both innate and adaptive immunity seem to play significant roles [17][18][19]. Accumulated data suggest that there is a mixed Th1/Th2/Th17 response during giardiasis [19,20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While the majority of Giardia infected individuals are asymptomatic, giardiasis is a major contributor to malnutrition and growth impairment in children from developing countries (Fink & Singer, 2017). Additionally, the disease may also last for a long term as a chronic infection.…”
Section: Discussionmentioning
confidence: 99%